Innovation in the treatment of aortic stenosis using 3D printing (Research, Society and Development, 2022)
The use of 3D pieces advances in a broader sense of education, towards interdisciplinarity. Several areas already use this technology to teach the academic community, even more complex research such as organ printing, and applications of design in prostheses. Current technology allows for the accurate printing of cardiac anatomy on materials that resemble the real properties of the heart and vessels, allowing the exploration of options, challenges, and possibilities of 3D printing in the field of valvular heart disease, to provide an insight into the current state of the art and development in this area specifically. Thus, the present study describes the potential in the teaching-learning process, regarding aortic stenosis, using Hands-on methodologies and models produced in a 3D printer. An integrative literature review was performed using the MeSH terms: “3d printing” and “aortic stenosis”. The advent of 3D printing technology can create anatomically accurate and patient-specific physical models, converting virtual 3D images on the computer's flat screen into palpable 3D models suitable for interventional simulation, allowing for a reduction in surgical time. The use of 3D printed models can facilitate the development of new devices and new surgical techniques. However, the limitations of this model still come up against the high cost, the image quality of the exam and the time for printing.